Ethnography Study about Fanaticism of “Figure Purwokerto” Community's Members - Rizki Setyo Nugroho; Muhammad Taufiqurrohman; Lynda Susana Widya Ayu Fatmawaty (Program Studi Sastra Inggris Universitas Jenderal Soedirman, 2021)
This research is aimed to figuring out the fanaticism from the members of an action figure community in Purwokerto called “Figure Purwokerto”. “Figure Purwokerto” community is an action figure community located in Purwokerto, Central Java, Indonesia. The total of the member is about 241 people from different age and culture. The researchers use focus group discussion and interview as the method to gain the information that the researcher needed for research purposes. The researchers applies some theories in order to obtain further analysis related to the issue. Fanaticism theory is used to figure out the fanaticism of “Figure Purwokerto” community’s members. Another theory, the Cultural Studies: Cultural Consumption Research, is added to make a deeper analysis about the consumption of culture from the members of the community. The scope of this research is cultural studies under the umbrella of English Studies which relates to American culture and supremacy with action figure as the media. Furthermore, the disscussion of this study is divided into two main parts which correspondent with the fanaticism happened in Figure Purwokerto community. The first part explains the portrayal of the fanaticism from the members of the community. The characteristics of a person can be said as a fanatics are included in this part. The second part explains the cultural relation between the members and the action figure as a culture. The result of this research concludes that the members are fanatic based on several aspects and characteristics of a fanatic. This research was also conducted to make another prespective of fanaticism which is seen as a bad term due to it’s relation to religion fanaticism.